Os recursos estratégicos territoriais e o desenvolvimento de vantagens competitivas para a região dos campos de cima da serra/RS - Andrade, Alessandro Dalla Santa (My University, 2014)
Themes involving regional development over time raised numerous theories and concepts to explain the phenomenon. With the globalization process this issue became even more complex and dynamic. In this universe, this work proposes the strategic territorial resources study in relation to their potential for generating competitive advantages for the regions. Thus, the literature has been related to the theory of Vision Based on Resources-VBR, globalizing theories and regionalist "development" issue, as well. Conjugation of VBR with the regionalist development theory allows the understanding of the dynamic process of construction in territorial competitive advantages, as it contributes to understanding of strategic support attributes of resources found in the territory. As a way to validate the study an investigation was carried out in the micro-region of ―Campos de Cima da Serra – Rio Grande do Sul State‖. Planning meetings were held with the territorial actors and institutions that make up the micro-regional governance, featuring it as a qualitative and exploratory research. Thus the document also discusses the importance of the role of regional governance for effective exploitation of strategic resources present in the territory. In this context, the study identified the strategic resources of the micro-region of ―Campos de Cima da Serra‖ as well as the attributes which give sustainability. Regarding the categories of resources in that micro-region, predominance was observed onto those considered "systemic" and linked to the natural conditions of the territory. This way the work emphasizes the current stage of development of the strategic resources in the micro-region of ―Campos de Cima da Serra‖ which noted opportunities for its efficient operation, considering that they are in different stages of development. Therefore the study concludes that the use of VBR as a tool for analysis and planning of micro-regions demonstrates strategic for efficient use of resources and timely for the possible generation of sustainable competitive advantages.
Os temas que envolvem o desenvolvimento regional, ao longo do tempo, abordaram inúmeras teorias e conceitos para explicar o fenômeno. Com o processo de globalização, esta temática tornou-se ainda mais complexa e dinâmica. Nesse universo, este trabalho propõe o estudo dos recursos estratégicos territoriais em relação ao seu potencial de geração de vantagens competitivas para as regiões. Deste modo, utilizou-se da bibliografia relacionada à Teoria da Visão Baseada em Recursos - VBR, bem como das teorias globalizante e regionalista da temática ―desenvolvimento‖. A VBR e a teoria do desenvolvimento regionalista permitem entender o processo dinâmico de construção de vantagens competitivas territoriais, pois contribuem para compreensão dos atributos de sustentação estratégica dos recursos encontrados no território. Como forma de validar o estudo, realizou-se uma investigação da microrregião dos Campos de Cima da Serra/RS. Foram realizados encontros de planejamento territorial com os agentes e instituições que compõem a governança microrregional, caracterizando a pesquisa como qualitativa e exploratória. Assim, o documento também aborda a importância do papel da governança regional para a efetiva exploração dos recursos estratégicos presentes no território. Neste contexto, o estudo identificou os recursos estratégicos dos Campos de Cima da Serra, bem como os atributos que lhe conferem sustentabilidade. No que diz respeito às categorias de recursos, observou-se a predominância daqueles considerados sistêmicos e ligados a condições naturais do território. Deste modo, o trabalho enfatiza o atual estágio de desenvolvimento dos recursos estratégicos dos Campos de Cima da Serra, dos quais se observaram oportunidades para sua eficiente exploração, sendo que estes se encontram em diferentes estágios de desenvolvimento. Portanto, conclui-se que o estudo da VBR, como teoria de análise e planejamento, contribui, substancialmente, para a compreensão do processo de criação de vantagens competitivas sustentáveis para as microrregiões.
Keywords: Planejamento regional - Serra, Região (RS); Economia regional - Serra, Região (RS); Planejamento estratégico; Strategic resources; Competitive advantages; Regional development